Ecological study of fishes in a small tropical stream (Sungai Kanching, Selangor, Peninsular Malaysia) and its tributaries - Mohd. Zakaria, -Ismail; Basir, Sabariah (Malaysian Journal of Science, 1994)
This paper presents the diversity and abundance of fishes in the Sungai Kanching and its tributaries, a second to fifth-order tropical stream. Fifteen species representing 8 families are found in the area. Ichthyofaunal composition is relatively diverse with an average Shannon-Weiner diversity index of 1.14. Standing biomass and number of individuals per m2 are 5.3 g and 0.4 indivi-duals, respectively. Poropuntius smedleyi, locally known as ikan daun, dominates the sampling sites not only in number but also in weight. Members of the Cyprinidae are the most common and abundant in the area. Early findings suggest that tropical streams which have been slightly disturbed may experience a reduction of standing biomass but not its species diversity. ABSTRAK -Malcalah ini memaparkan keanikaan dan kelimpahan ilcan di Sungai Kanching serta anak-anak sungainya yang berorder ke-2 hingga ke-5. Lima betas spesies yang merangkumi 8 famili ikan terdapat di kawasan kajian. Komposisi iktiofauna kawasan ini agak tinggi denganpurata indeks kepelbagaian Shannon-Weiner sebanyak 1.14. Biomassa tegakan dan bilangan individu untuk 1 m2masing-masing 5.3 g dan 0.4 individu. Poropuntius smedleyi, yang dikenali sebagai ikan daun, adalah spesies ikan yang paling dominan bukan sahaja dari segi jumlah individu tetapi juga berat. Spesies-spesies ikan Cyprinidae merupakan kumpulan yang paling dominan. Pene-muan awal menunjukkan anak-anak sungai di kawasan tropika yang mengalami tahap gangguan yang agak minima akan mengalami pengurangan dan segi biomassa tegakan. Bergantung kepada tahap gangguan yang dialami oleh anak-anak sungai tersebut, keanikaan ikan mungkin tidak berubah. (ecology, stream, fish, Cyprinidae, diversity)